Postoperative vocal fold palsy in patients undergoing thyroid surgery with continuous or intermittent nerve monitoring. Issue 11 (2nd September 2015) - Schneider, R.; Sekulla, C.; Machens, A.; Lorenz, K.; Nguyen Thanh, P.; Dralle, H.
<x xml:space="preserve">Abstract</x> Background Continuous monitoring of electromyographic (EMG) amplitudes of the vocal muscles detects impending injury of the recurrent laryngeal nerve (RLN) during thyroid operations earlier than intermittent EMG monitoring. This may alert the surgeon to stop a manoeuvre causing stretching or pressure on the RLN, with better recovery of nerve function. Methods Patients with intact preoperative RLN function who underwent thyroid surgery for benign disease between January 2011 and September 2014 under continuous intraoperative nerve monitoring (CIONM) or intermittent intraoperative nerve monitoring (IIONM) were included in this observational study conducted at a tertiary surgical centre. For CIONM, combined EMG events indicative of imminent nerve injury were defined as an EMG amplitude decrease of 50 per cent or more and a latency increase of 10 per cent relative to baseline values. The rates of early and permanent palsy for the two groups of patients were compared. Results There were 1526 patients, 788 of whom (1314 nerves at risk) underwent thyroid surgery using CIONM and 738 (965 nerves at risk) had IIONM. With the use of CIONM, 63 (82 per cent) of 77 combined events were reversible during the operation. No permanent vocal fold palsy occurred with CIONM, whereas four unilateral permanent vocal fold palsies (0·4 per cent) were diagnosed after IIONM (P = 0·019). Conclusion Operation with CIONM resulted in fewer permanent vocal fold palsies compared with IIONM after thyroid surgery in patients with benign disease.